Methodological Approach Into Researching Traffic Under Extraordinary Security Circumstances - Ercegovac, Peter-Anthony; Kolenc, Jurij (Promet - Traffic&Transportation, 2008)
The complexity of researching traffic under extraordinaryconditions in order to implement a more efficient and functionaltraffic management strategy under both normal and irregularconditions- as well as the grey zone of when the changefrom normal into extraordinary traffic conditions actually occur-provides the researcher with numerous methodologicalproblems.Starting from the viewpoint that the field of traffic scienceneeds an increase into the capacity of research into traffic underextraordinary conditions we have chosen to define withinthis article a specific methodological approach that undertakesa study into the exposure, menace, threat and risk faced by trafficsystems under extraordinary conditions through utilisingmethods utilised by the military that allow for the possible resolutionof such problems through compatible testing of both simulatedand real life conditions that such systems may face.In searching for possible applicable solutions to such demandingparametres we believe that the use of concrete informationin real time and real space in order to bring about amore efficient functioning of traffic under extraordinary conditionscan be achieved through the use of the analytical capacityof traffic systems information gathering attained through theusage of Uninhabited Flying Vehicles (UFVs) in monitoringroad, rail and maritime traffic and transport.